Anaplastic pancreas carcinoma diagnosed by fine needle aspiration biopsy technique - (:unkn) unknown (My University, 2011)
0
İnce iğne aspirasyon biyopsi tekniği ile teşhis edilen anaplastik pankreas karsinomu
Keywords: Cerrahi